Clinical Effect of Emergency Dermabrasion Combined with Biological Dressing A on Wound Microcirculation and Preventing Sepsis in Deep Degree-II Burns. (14th July 2022) - Shao, Huawei; Luo, Ru; You, Chuangang; Li, Qiong; Mao, Shulei
Abstract : Objective . The aim of this study is to explore the clinical effect of emergency dermabrasion combined with biological dressing A on wound microcirculation and preventing sepsis in deep degree-II burns. Methods . A total of 90 patients with deep degree-II burns admitted to the hospital were retrospectively enrolled between January 2020 and January 2022. According to different treatment methods, they were divided into the control group (42 cases, biological dressing A) and the observation group (48 cases, emergency dermabrasion combined with biological dressing A). The clinical curative effect in both groups was observed. The wound repair rate and wound healing quality, and changes in levels of wound microcirculation-related indexes (serum epidermal growth factor (EGF), wound blood flow, and partial pressure of transcutaneous oxygen) and inflammatory cytokines (C-reactive protein (CPR), interleukin-6 (IL-6), erythrocyte sedimentation rate (ESR), and procalcitonin (PCT)) before treatment, at 3d and 7d after treatment were compared between the two groups. The incidence of wound infection and sepsis in both groups was recorded. Results . The wound healing time in the observation group was significantly shorter than that in the control group, and wound healing quality in the observation group was better than that in the control group (P < 0.05 ). At 3 d and 7d after treatment, the levels of serum EGF, wound blood flow and partial pressure of transcutaneous oxygen in both groups were all increased (P < 0.05 ), which were higher in the observation group than those in the control group (P < 0.05 ). The levels of CRP, IL-6, ESR, and PCT in both groups were all decreased (P < 0.05 ), which were lower in the observation group than those in the control group (P < 0.05 ). There was no significant difference in incidence of sepsis between observation group and control group (4.17% (2/48) vs. 7.14% (3/42)) ( Fisher  = 0.539). Conclusion . Emergency dermabrasion combined with biological dressing A can effectively improve wound microcirculation in patients with deep degree-II burns, promote wound healing, shorten wound healing time, improve wound healing quality, effectively control inflammatory response, and prevent sepsis.